The Supernova Multiplier : Crossing the Invisible Bridge to Exceptional Client Service and Consistent Growth. - Knapp, Robert D. (John Wiley & Sons, Incorporated, 2019)
Take your Supernova practice to even greater heights of performance and profitability The Supernova Multiplier provides expert guidance to the revolutionary wealth management model that has transformed the lives and businesses of financial professionals worldwide. The innovative Supernova method enables financial advisors to rapidly grow their business, efficiently manage time, and maximize client satisfaction. The Five Stars of the Supernova model--Segmentation, Organization, Planning, Acquisition, and Leadership--provide financial advisors with the tools and knowledge to propel their practices to new heights of performance. The acknowledged pioneer of the Supernova model, author Rob Knapp offers in-depth examination of every aspect of the Supernova model, from client experience to leadership development. This invaluable resource addresses significant issues facing disciples of the model, including areas of chronic underperformance, and delivers proven solutions that financial advisors can integrate into their practices. Detailed coverage of core elements, such as the Rule of Reciprocity, Gap Analysis and the Five Star Model, promotes critical analysis of advisor performance and builds the foundation for precise alignment to the essential Supernova principles. This indispensable book empowers current and prospective Supernova practitioners to: Build and optimize an efficient and profitable Supernova advisory practice Structure your practice around high-value activities that increase revenue and grow your business Maintain a predictable schedule of meaningful client contact Develop and implement proactive planning strategies with your team and client base. The Supernova model is not complex, but requires sustained and disciplined effort to achieve best results. The Supernova Multiplier: 7 Strategies for Financial Advisors to Grow Their Practices is the key to unlocking remarkable results and sustained achievement in advisory practices across the financial management industry that will differentiate you and your practice from the ordinary into the extraordinary.